The utility of software-detected non-invasive tear break-up in comparison to fluorescein tear break-up measurements - Pflugfelder, Stephen C.; Kikukawa, Yasushi; Tanaka, Shin; Kosugi, Takuya (Frontiers in Medicine, 2024)
The purpose of this study is to characterize and discuss the difference between software-detected noninvasive tear break-up time (NIBUT) and the traditional clinical method of fluorescein break-up time (FBUT).Methods: Tear interferometry with the KOWA DR-1α (Kowa, Japan) and a standardized comprehensive ocular surface/tear evaluation were performed in 307 eyes. Softwaredetected NIBUT in the KOWA DR-1α images and the investigator-detected FBUT were compared.Results: Software detected NIBUT was significantly shorter than investigator measured FBUT. NIBUT was 3.1 ± 2.5 seconds (mean ±SD), whereas FBUT was 4.8 ± 3.0 seconds. Three types of patterns/conditions contributed to this difference: spot break immediately after eyelid opening, moderate to severe keratitis sicca, and epithelial basement membrane corneal dystrophy (EBMD). Rapid tear film disruption was not captured by FBUT in these cases. Spot break immediately after eye opening that rapidly disappears was observed with conjunctivochalasis. This type of break-up may be difficult to detect with fluorescein because the human eye cannot catch such rapid blinks or post-blink events. In the 2nd group with severe corneal epithelial disease break-up may occur over the entire corneal surface upon eye opening and distinct fluorescein tear break-up may not be identified because of poor dye dilution or spread over the corneal surface, whereas the noninvasive break-up is not solution dependent, and the software can detect a district appearance. In the 3rd group with EBMD, it is possible that focal break-up in the fluorescein pattern over the epithelial elevations that is missed visually can be detected by software in video images.